An Analysis of School Counselors’ Creative Personality in West Bandung Regency - Maryani, Ineu; Ahman, Ahman; Nurihsan, Juntika; Ilfiandra, Ilfiandra (Academia Edu Cendekia Indonesia (AEDUCIA), 2022)
Personality is one of the aspects of a school counselor’s professional competence, which is shown by the ability to carry out creative and innovative services. This study aims to profile and analyze school counselors’ creative personalities in West Bandung Regency. This survey study distributed a creative personality questionnaire through Google Form to sixty-eight school counselors in junior high schools in West Bandung Regency. The study result showed that 18% of the participants have low creativity, 60% have moderate creativity, and 22% have high creativity. Further scrutiny through subvariable analysis showed that 19% of participants have low creativity in terms of product, while 56% and 25% have moderate and high creativity, respectively. Regarding participants’ creative attitude, 12% exhibited a low attitude, 69% exhibited a moderate attitude, and 19% exhibited a high attitude toward creativity. Lastly, 18% of participants have low creative behaviors, 68% have moderate creative behaviors, and 16% have high creative behaviors. The result of this study could be used as empirical data for developing school counselors’ creativity.